The goals of private law - Robertson, Andrew, 1966-; Tang, Hang Wu (Hart Pub., 2009)
This collection contributes to a fundamentally important set of debates about the nature of private law. The essays consider whether private law should be seen as having goals and, if so, whether those goals are particular to private as opposed to public law. They consider the legitimacy of the pursuit of community welfare goals in private law and the place of instrumentalist thinking in private law scholarship. They explore the relationship between the pursuit of policy goals and the other influences that shape private law, such as the formal values of certainty, consistency and coherence and.